Duality in property: Commons and anticommons - Francesco Parisi; Norbert Schulz; Ben Depoorter (University of Würzburg, Department of Economics, 2000)
Commons and Anticommons problems are the consequence of symmetric structural departures from a unified conception of property. In this paper, we endeavor to provide a dual model of property, where commons and anticommons problems are the consequence of a lack of conformity between use and exclusion rights. The general model is then extended to consider the different equilibria obtained under vertical and horizontal cases of property fragmentation. The paper concludes with a hypothesis of legal rules for promoting unity in property and suggests a list of possible areas of application.
Keywords: 330